Pengembangan Media Pembelajaran Game Edukasi pada Mata Pelajaran Bahasa Arab Kelas VIII di SMP - Akbar, Kihsan Ramdana; Hendri, Nofri; Eldarni, Eldarni; Pratiwi, Rahmi (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop educational game learning media in grade VIII Arabic subjects in junior high school. The research was conducted using the type of research and development (R&D) with the Hannafin and Peck development model. The data collection instruments in this study used validation sheets, student response questionnaires, and post-test pre-test questions. The validity of the product was tested by two media experts and one material expert. The practicality test was aimed at grade VIII students of SMP Muhammadiyah 6 Padang. Pre-test and post-test scores are used to assess the effectiveness of using educational games. Based on the results of the assessment from the media and material validators, the results of material validation 4.5 were categorized as valid. For the media aspect, a score of 4.93 was obtained from media expert 1, which is in the valid category, while media expert 2 with a score of 4.67 in the valid category. After the media was declared valid and feasible, it was then tested on 26 students in grade VIII of junior high school with a practicality score of 0.72 in the practical category. The effectiveness test was carried out with a G-Score of 0.73 in the high effectiveness category, so that the use of educational game learning media was declared effective because there was a significant difference between learning values before and after using educational games. It can be concluded that the educational game learning media that has been developed is valid, practical, and effective to be used in learning Arabic